PEMBERDAYAAN MASYARAKAT GOHENG DAN SEKITARNYA DI MEUNASAH NAHDATUL FATAH DESA LAMTEUMEN TIMUR KECAMATAN JAYA BARU KOTA BANDA ACEH - Rosma ely; Hajidin Hajidin.; monawati monawati. (Universitas Syiah Kuala, 2019)
ABSTRACT This article describes an empowerment activity conducted to train various alternative skillsopportunities for Goheng community in order to try to increase their income so that they canimprove their economy and their surroundings. In line with the objectives, the targets to beachieved is 20 housewives who can skillfully knit a total of 20 wallets and 60 brooches, 19housewives and 1 male who can skillfully decorate with henna, 2 males and 18 housewiveswho are skilled in massage.